(untitled) (Scientific journal of the Fergana State University, 2023)
This article presents the method of synthesis of m-ferrocenyl benzoic acid with methyloldithiourea and the results of IR spectroscopy and mass spectrometry analysis proving the structure of the new substance obtained.